(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the linguacognitive features of lexical enantiosemy using the example of English, Russian and Uzbek languages. The author, analyzing the works of M.Yu. Brodsky and L.R. Makhmutova, considers the classification of lexical enantiosemy, including such types as complete and incomplete, regular and irregular, as well as various types (synchronic, diachronic, internal and interlingual). The article considers examples of lexical enantiosemy, such as the English words dreadful, ever, repose and fame, as well as their analogues in Russian and Uzbek. In addition, attention is paid to phraseological enantiosemy, where examples such as to be death on something and Russian expressions with the preposition "bez" – without demonstrate opposite meanings in context. The study emphasizes the importance of contextual interpretation for understanding enantiosemy in different languages.